Menyelami Esensi: Integrasi Ilmu Pengetahuan dan Teknologi dalam Kurikulum Pendidikan Agama Islam - Ghina Rahmah Maulida (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Each period experiences an important transformation in Islamic religious education, which requires the development of an accurate curriculum with a strong foundation to achieve clear targets. This paper aims to investigate the contribution of curriculum development principles in the context of Islamic religious education. The writing method used is library research using scientific journals, books and online sources. The findings show how crucial a comprehensive understanding of the Islamic education curriculum, knowledge and science is, as well as the influence of scientific thinking on the progress of science and technology. This article emphasizes that the Islamic education curriculum goes beyond academic boundaries by integrating spiritual and moral aspects to form a generation that God-fearing. In addition, knowledge and science play an important role in education, while the philosophy of science guides the direction of the development of science and technology.